Long-term leachability of Sb in smelting residue stabilized by reactive magnesia under accelerated exposure to strong acid rain. (1st January 2022) - Zhang, Ying; Lu, Xuxing; Yu, Rongda; Li, Jining; Miao, Jiahe; Wang, Fenghe
Abstract: This study investigated the long-term leachability of antimony (Sb) in a smelting residue (39519 mg/kg) solidified/stabilized by reactive magnesia (MgO). Different dosages of MgO (0% as control, 2%, 5%, and 10% on a dry basis) were compared, and the long-term performance was evaluated by an accelerated exposure test consist of 20 consecutive leaching steps with simulated strong acid rain (SAR, HNO3 : H2 SO4 = 1:2, pH = 3.20) as the extractant. Notably, the MgO treatments efficiently reduced the Sb leachability. Compared to the original slag (8.3 mg/L), the leaching concentrations based on a Chinese standard HJ/T299-2007 were reduced by 58%, 79%, 85%, and 86% at MgO dosages of 0%, 2%, 5%, and 10%, respectively. Because the studied slag was rich in oxides like SiO2, CaO, and MgO, the hydration reactions probably happened during the aging processes with oxic water. It was inferred that the formed hydration products have a self-solidification/stabilization function to suppress the Sb leaching from the solid phase. The mineralogical characterization results proved that the hydrated Mg(OH)2 played an essential role in the decrease of Sb leachability. Besides, the MgO addition promoted the hydration of this smelting slag and formed new hydrate gels that immobilize Sb in this slag. Our results confirmed that MgO-amended slags were resistant to continuous SAR corrosion. Compared to the control, the dosage of 5% MgO could effectively reduce the cumulatively released Sb by 57%, with only 0.46% of total Sb could be leached. The decomposition of Mg(OH)2 and hydrate gels determined the re-release of Sb in a long term. Our work has demonstrated that reactive MgO amendment could be potentially selected as an effective strategy for the treatment of Sb-containing smelting residues in field conditions. Graphical abstract: Image 1 Highlights: The Sb in smelting slag was effectively solidified/stabilized by reactive MgO. Formation of hydrated Mg(OH)2 and gel materials contributed to the decrease in Sb leachability. Mg(OH)2 and gel materials stability controlled the S/S efficiency when exposed to SAR. Cumulative released Sb reduced by 57% after 5% MgO treatment under accelerated SAR exposure.